Penerapan Model Pembelajaran Make a Match untuk Meningkatkan Hasil Belajar PAI dan Budi Pekerti Peserta Didik Kelas V SDN 176/X Majelis Hidayah Tahun pada Semester Ganjil Ajaran 2021/2022 - Khodijah Khodijah (Journal on Education, 2022)
This research is motivated by the learning outcomes of students towards PAI learning are still low and an effort is needed to improve it. The purpose of this study was to obtain information and discuss the application of the make a match learning model to improve PAI (Islamic Education) and character learning outcomes for fifth grade students of SDN 176/X Majelis Hidayah for the academic year 2021/2022. This type of research is classroom action research which consists of two cycles with each cycle consisting of four stages, namely planning, implementation, observation, and reflection. This research was carried out at SDN 176/X Majelis Hidayah in the odd semester of the academic year 2021/2022 with the research subjects being class V students at SDN 176/X Majelis Hidayah, totaling 17 students. Data collection techniques using tests, field notes, interviews, and documentation. Data were analyzed using percentages and data reduction. The results showed that through the cooperative learning model the make a match type could improve the understanding of PAI and Budi Pekerti learning of students in class V SDN 176/X Majelis Hidayah by giving rewards.